Reading experimental writing - Colby, Georgina (Edinburgh University Press, 2019)
Bringing together internationally leading scholars whose work engages with the continued importance of literary experiment, this book takes up the question of 'reading' in the contemporary climate from culturally and linguistically diverse perspectives